Role of Rutin on Nitric Oxide Synthesis in Human Umbilical Vein Endothelial Cells. (24th June 2014) - Ugusman, Azizah; Zakaria, Zaiton; Chua, Kien Hui; Megat Mohd Nordin, Nor Anita; Abdullah Mahdy, Zaleha
Abstract : Nitric oxide (NO), produced by endothelial nitric oxide synthase (eNOS), is a major antiatherogenic factor in the blood vessel. Oxidative stress plays an important role in the pathogenesis of various cardiovascular diseases, including atherosclerosis. Decreased availability of endothelial NO promotes the progression of endothelial dysfunction and atherosclerosis. Rutin is a flavonoid with multiple cardiovascular protective effects. This study aimed to investigate the effects of rutin on eNOS and NO production in cultured human umbilical vein endothelial cells (HUVEC). HUVEC were divided into four groups: control; oxidative stress induction with 180  μ M H2 O2 ; treatment with 300  μ M rutin; and concomitant induction with rutin and H2 O2 for 24 hours. HUVEC treated with rutin produced higher amount of NO compared to control (P < 0.01 ). In the oxidative stress-induced HUVEC, rutin successfully induced cells' NO production (P < 0.01 ). Rutin promoted NO production in HUVEC by inducing eNOS gene expression (P < 0.05 ), eNOS protein synthesis (P < 0.01 ), and eNOS activity (P < 0.05 ). Treatment with rutin also led to increased gene and protein expression of basic fibroblast growth factor (bFGF) in HUVEC. Therefore, upregulation of eNOS expression by rutin may be mediated by bFGF. The results showed that rutin may improve endothelial function by augmenting NO production in human endothelial cells.